Time-of-Flight Cameras and Microsoft Kinect™ - Dal Mutto, Carlo; Zanuttigh, Pietro; Cortelazzo, Guido M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Time-of-Flight Cameras and Microsoft Kinect™ closely examines the technology and general characteristics of time-of-flight range cameras, and outlines the best methods for maximizing the data captured by these devices. This book also analyzes the calibration issues that some end-users may face when using these type of cameras for research, and suggests methods for improving the real-time 3D reconstruction of dynamic and static scenes. Time-of-Flight Cameras and Microsoft Kinect™ is intended for researchers and advanced-level students as a reference guide for time-of-flight cameras. Practitioners working in a related field will also find the book valuable.
Introduction -- CW Matricial Time-of-Flight Range Cameras -- Microsoft Kinect™ Range Camera -- Calibration -- Fusion of Depth Data with Standard Cameras Data -- Scene Segmentation and Video Matting Assisted by Depth Data -- Conclusions.
Keywords: Signal processing; Image processing; Speech processing systems; Optical data processing; Pattern recognition; Signal, Image and Speech Processing; Image Processing and Computer Vision; Pattern Recognition